Coworker networks and the labor market outcomes of displaced workers: Evidence from Portugal - Garcia‐Louzao, J.; Silva, M. (Industrial Relations, 2024)
The use of social contacts in the labor market is widespread. This paper investigates the association between personal connections and hiring probabilities as well as re-employment outcomes of displaced workers in Portugal. The hiring analysis indicates that displaced workers with a direct link to a firm through a former coworker are three times more likely to be hired compared to workers displaced from the same closing event who lack such a tie. Moreover, we show that successful displaced workers with a connection in the hiring firm have higher entry-level wages and enjoy greater job security.